Language city : the fight to preserve endangered mother tongues in New York - Perlin, Ross (Atlantic Monthly Press, 2024)
"From the co-director of the Endangered Language Alliance, a captivating portrait of contemporary New York City through six speakers of little-known and overlooked languages, diving into the incredible history of the most linguistically diverse place ever to have existed on the planet. Half of all 7,000-plus human languages may disappear over the next century and--because many have never been recorded--when they're gone, it will be forever. Ross Perlin, a linguist and co-director of the Manhattan-based non-profit Endangered Language Alliance, is racing against time to map little-known languages across the most linguistically diverse city in history: contemporary New York. In Language City, Perlin recounts the unique history of immigration that shaped the city, and follows six remarkable yet ordinary speakers of endangered languages deep into their communities to learn how they are maintaining and reviving their languages against overwhelming odds. Perlin also dives deep into their languages, taking us on a fascinating tour of unusual grammars, rare sounds, and powerful cultural histories from all around the world. Seke is spoken by 700 people from five ancestral villages in Nepal, a hundred of whom have lived in a single Brooklyn apartment building. N'ko is a radical new West African writing system now going global in Harlem and the Bronx. After centuries of colonization and displacement, Lenape, the city's original Indigenous language and the source of the name Manhattan ("the place where we get bows"), has just one fluent native speaker, bolstered by a small band of revivalists. Also profiled in the book are speakers of the Indigenous Mexican language Nahuatl, the Central Asian minority language Wakhi, and the former lingua franca of the Lower East Side, Yiddish. A century after the anti-immigration Johnson-Reed Act closed America's doors for decades and on the 400th anniversary of New York's colonial founding, Perlin raises the alarm about growing political threats and the onslaught of "killer languages" like English and Spanish. Both remarkable social history and testament to the importance of linguistic diversity, Language City is a joyful and illuminating exploration of a city and the world that made it"--